Carrier phase recovery without pilot symbols for non-differential coherent receivers - Castrillon, Mario A. (2016)
Fil: Castrillon, Mario A. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Estudios Avanzados en Ingeniería y Tecnología; Argentina.